Penerapan Metode Pembelajaran Discovery Learning Pada Mata Pelajaran Fiqih Di MTs Tarbiyatul ‘Ulum Tirtomoyo-Kebumen - Alifah, Anisa Rizki; Trisnawati, Oky Ristya (Tarbi: Jurnal Ilmiah Mahasiswa, 2025)
Education is the key to all quality progress and renewal. To create a quality learning process, the right method is needed. Discovery learning method is the right method because the process of learning activities is led by students. This research is a quantitative experimental research. The students studied were class VIII students of MTs Tarbiyatul 'Ulum Tirtomoyo. The number of students studied in the experimental class was 16 students and in the control class were 15 students. The data analysis used was the independent simple t test and the prerequisite tests were carried out, namely the normality test and homogeneity test. The results of this study are: (1) The application of the discovery learning method in the Fiqh subject has 3 activities carried out, namely: 1) preliminary activities; 2) core activities; 3) closing activities. (2) The discovery learning method can improve student learning outcomes, seen from the results of the posttest average score of experimental class students using the discovery learning method of 89.06, while the posttest average value of the control class using conventional methods is 81.33. This shows that there are differences in student learning outcomes in the experimental class and the control class. So that learning using the discovery learning method is more effective in improving student learning outcomes in fiqh subjects in class VIII MTs Tarbiyatul 'Ulum Tirtomoyo